All-solid-state electrolyte film and preparation method thereof

By high entropy on the garnet oxide solid electrolyte layer and depositing amorphous electrolyte buffer layer on both sides, an electrolyte film with a sandwich structure is formed, the shortcomings of the existing garnet electrolyte in terms of interface contact, ionic conductivity and mechanical properties are solved, and the application of high-performance solid lithium batteries is realized.

CN119725703APending Publication Date: 2025-03-28TIANFU JIANGXI LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967334.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing garnet solid electrolytes have shortcomings in interface contact, ionic conductivity and mechanical properties, resulting in cracks or brittle fractures in the film during preparation, and poor solid-solid contact affects ionic conductivity.

Method used

A highly entropy garnet-type oxide solid electrolyte layer is used, and an amorphous electrolyte buffer layer is deposited on both sides of it to form an electrolyte film with a sandwich structure. The structure and performance of the film are optimized by magnetron sputtering deposition of the amorphous buffer layer and low-temperature sintering heat treatment.

Benefits of technology

It improves the ionic conductivity of the electrolyte, enhances the interface stability and mechanical properties, avoids cracks and brittle fracture problems in the film during the preparation process, and improves the overall performance of solid-state lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725703A_ABST
    Figure CN119725703A_ABST
Patent Text Reader

Abstract

The invention discloses an all-solid-state electrolyte film and a preparation method thereof, the electrolyte film comprises a garnet type oxide solid electrolyte layer and an amorphous electrolyte buffer layer, the garnet type oxide solid electrolyte layer is a high-entropy electrolyte layer, and the amorphous electrolyte buffer layer is an amorphous electrolyte buffer layer. The amorphous electrolyte buffer layers are deposited on two sides of the garnet type oxide solid electrolyte layer to form an electrolyte film with a sandwich structure. The garnet type oxide solid electrolyte is subjected to high entropy, the problem that the ionic conductivity of the garnet type oxide solid electrolyte layer is low is solved, meanwhile, the electrolyte film of a sandwich structure is designed, and amorphous electrolyte buffer layers are deposited on the two side faces of the garnet type oxide solid electrolyte layer, so that the ionic conductivity of the garnet type oxide solid electrolyte layer is improved. The garnet oxide solid electrolyte is optimized by utilizing the modification effect of the amorphous buffer layer, so that the problems of cracks and brittle fracture when an electrolyte film is prepared by adopting a garnet type electrolyte are solved, and the related problems of solid-solid contact with an electrode are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to an all-solid electrolyte film and a preparation method thereof. Background Art

[0002] As an emerging battery technology, solid-state thin-film batteries are gradually becoming an important direction in battery miniaturization and industrial development. Compared with traditional liquid electrolyte-based lithium-ion batteries, solid-state batteries have significant advantages, especially in terms of safety and cost control. Replacing liquid electrolytes with solid electrolytes not only avoids flammable components in liquid electrolytes, but also effectively solves safety hazards such as battery fires and explosions, providing a safer and more reliable option for the widespread application of new energy vehicles.

[0003] At present, the research on solid electrolytes is mainly focused on inorganic materials such as oxides, sulfides and nitrides, among which oxide inorganic solid electrolytes are considered to be one of the most promising solid electrolytes. Garnet-type solid electrolytes usually have excellent structural stability, and their unique crystal structure provides a good migration channel for lithium ions. However, the ion conductivity of garnet-type electrolytes is low, and due to their relatively hard and brittle nature, they may cause cracks or brittle fractures in the film during the preparation process, and the interface stability and mechanical properties are adversely affected. These two points seriously limit their application in high-performance batteries. At the same time, when using garnet-type solid electrolytes to make batteries, due to the solid-solid contact with the electrodes on both sides, it will lead to poor solid-solid contact, which further has an adverse effect on ionic conductivity.

[0004] In view of this, this patent application is filed. Summary of the invention

[0005] In order to solve the technical bottlenecks faced by current solid electrolytes in terms of interface contact, ionic conductivity and mechanical properties, the present invention provides an all-solid-state electrolyte film and a preparation method thereof to solve the above technical problems.

[0006] The present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide an all-solid-state electrolyte film, comprising a garnet-type oxide solid electrolyte layer and an amorphous electrolyte buffer layer, wherein the garnet-type oxide solid electrolyte layer is a high-entropy electrolyte layer, and the amorphous electrolyte buffer layer is deposited on both sides of the garnet-type oxide solid electrolyte layer to form a sandwich-structured electrolyte film.

[0008] In order to solve the current problems of solid-solid contact and ionic conductivity between solid electrolytes and electrodes, the present invention firstly performs high entropy treatment on garnet-type oxide solid electrolytes to obtain a high entropy electrolyte layer, which has better ionic conductivity based on the high entropy effect, and solves the problem of low ionic conductivity of the garnet-type oxide solid electrolyte layer. Secondly, the inventors designed an electrolyte film with a sandwich structure, deposited an amorphous electrolyte buffer layer on both sides of the garnet-type oxide solid electrolyte layer, and optimized the garnet oxide solid electrolyte by using the modification effect of the amorphous buffer layer. The amorphous buffer layer has better processability and lower Young's modulus, which solves the problems of cracks and brittle fractures that occur when only garnet-type electrolytes are used to prepare electrolyte films, as well as solves the problems related to solid-solid contact with electrodes, and improves interface stability and mechanical properties.

[0009] As a preferred design, the composition of the garnet-type oxide solid electrolyte layer is Li 6.4 Ln3Z 1.2 Ti 0.8 V 0.8 O 12 , referred to as LLZTVO.

[0010] In the present invention, by rationally designing the composition and proportion of the garnet-type oxide solid electrolyte layer and utilizing its highly complex composition, the obstacles to ion migration in traditional solid electrolytes can be eliminated while maintaining the superionic conductive structure of the electrolyte.

[0011] As a preferred design, the amorphous electrolyte buffer layer is a buffer layer of any one of amorphous LiPON, aluminum oxide, silicon oxide, and aluminum fluoride;

[0012] Preferably, the aluminum oxide is aluminum oxide, and the silicon oxide is silicon dioxide.

[0013] As a preferred design, the thickness of the garnet oxide solid electrolyte layer is 0.4-2 μm, and the thickness of the amorphous electrolyte buffer layer is 300-500 nm.

[0014] As a preferred design, the deposition of the amorphous electrolyte buffer layer is magnetron sputtering deposition.

[0015] In the present invention, magnetron sputtering technology is used to deposit the amorphous electrolyte buffer layer, which can obtain a dense film at the atomic level, thereby reducing the interface resistance, improving the ionic conductivity of the electrolyte, and synergistically enhancing the ionic conductivity with high entropy.

[0016] The second object of the present invention is to provide a method for preparing the all-solid electrolyte film as described in any one of the above, comprising the following steps:

[0017] (1) preparing a high entropy garnet solid electrolyte layer;

[0018] (2) using the prepared high entropy garnet solid electrolyte layer as a substrate, magnetron sputtering deposition is performed on both sides of the substrate to form an amorphous electrolyte buffer layer, thereby obtaining a sandwich-structured electrolyte film;

[0019] (3) The sandwich-structured electrolyte film obtained above is subjected to low-temperature sintering heat treatment to obtain an all-solid-state electrolyte film.

[0020] In the present invention, a high entropy garnet solid electrolyte layer is first obtained, and then magnetron sputtering deposition is performed on both sides of the high entropy garnet solid electrolyte layer as a substrate, so that a uniform thickness and dense film layer can be obtained, and the film forming speed and quality can be precisely adjusted; finally, a low-temperature sintering heat treatment is used, which can promote the diffusion of ions between layers, making the bonding performance between layers in the sandwich structure stronger, and has a significant effect on improving the conductivity of the entire material, thereby obtaining an integrated sandwich structure thin film solid electrolyte with stronger processability and more stable structure. Figure 1 The sandwich structure electrolyte membrane material of the present invention is shown in FIG. Figure 2 A flow chart of the preparation method of the present invention is given.

[0021] The use of this magnetron sputtering process and integrated sandwich structure makes the structure have the characteristics of fast ion transmission and electronic insulation, effectively inhibiting the interface reaction between the solid electrolyte and the electrode, and ensuring that the electrolyte film has high ionic conductivity while having good interface contact, high stability, excellent processing performance, and good flexibility. It has outstanding application prospects in the design and development of high-energy and long-life solid-state lithium batteries.

[0022] As a preferred design, the process in step (1) is:

[0023] According to the formula of the garnet-type oxide solid electrolyte layer, raw materials are weighed;

[0024] The raw materials are mixed and wet-milled, isopropanol or ethanol is used as a dispersant during the ball milling process, zirconium balls are used as the ball milling medium, the ball milling speed is set to 400-500 r / min, and the ball milling time is preferably designed to be 12 hours; then dried to obtain a uniform high-entropy garnet precursor powder;

[0025] Then, the high entropy garnet precursor powder is calcined at 850-900°C for 6 hours, and the heating rate is controlled at 3-5°C / min during the process to ensure the uniformity and full reaction of the material; the calcination atmosphere is an air atmosphere to obtain a calcined powder;

[0026] The calcined powder is mixed with a binder (such as polyvinyl alcohol or sodium polyacrylate) and then cold-pressed at 30-50 MPa to form a high-entropy garnet electrolyte embryo. Finally, the formed high-entropy garnet electrolyte embryo is sintered at 1000-1100° C. for 8-12 hours and then cooled to room temperature.

[0027] As a preferred design, in step (2), the temperature of the high entropy garnet solid electrolyte layer as the substrate is 50-120° C.;

[0028] And / or, during the magnetron sputtering deposition process, the sputtering power is 50 to 200 W and the deposition time is 15 to 30 minutes.

[0029] The inventors have found that in the process of sputtering an amorphous buffer layer, in-situ heating of the sputtered substrate within a certain temperature range can increase the surface migration ability of the sputtered amorphous buffer layer material, reduce the accumulation of stress in the film, make the atoms in the film more tightly arranged, reduce the porosity, and increase the density of the film. Furthermore, the temperature of the high-entropy garnet solid electrolyte layer of the substrate is set to 50-120°C, which can avoid the decomposition of the substrate material and help the amorphous material to form an ordered structure. In the magnetron sputtering deposition process, the sputtering power is set to 50-200W and the deposition time is 15-30 minutes, which is the power and time range for sputtering amorphous LiPON, aluminum oxide, silicon oxide, and aluminum fluoride materials.

[0030] As a preferred design, after magnetron sputtering is completed, the deposited film is annealed at room temperature for 10 to 30 minutes. Annealing can further optimize the structure of the film and reduce stress.

[0031] As a preferred design, during the low-temperature sintering heat treatment in step (3), the sintering temperature is 200-500° C. and the time is 1-4 hours.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] The high-entropy all-solid electrolyte film LLZTVO provided by the present invention adopts a high-entropy synthesis strategy, which can effectively regulate the ionic conductivity, electrochemical window, etc. of the solid electrolyte. A thin film solid electrolyte with a sandwich structure is prepared by further introducing an amorphous electrolyte buffer layer by magnetron sputtering. The amorphous electrolyte forms an efficient and good contact at the atomic level with the high-entropy electrolyte and the electrode, and further promotes interlayer ion diffusion by low-temperature sintering to form an integrated sandwich structure thin film solid electrolyte with stronger processability and more stable structure. The magnetron sputtering process and the integrated sandwich structure can effectively modify the positive and negative electrode interfaces, so that the structure has the characteristics of fast ion transmission and electronic insulation, effectively inhibits the interface reaction between the solid electrolyte and the electrode, and can ensure that the electrolyte film has the advantages of good interface contact, high stability, excellent processing performance, and good flexibility while having high ionic conductivity. It has outstanding application prospects in the design and development of high-energy and long-life solid-state lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0035] Figure 1 This is a schematic diagram of the sandwich structure electrolyte membrane material of the present invention.

[0036] Figure 2 The present invention is a flow chart of the method for preparing the electrolyte membrane. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0038] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0039] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0040] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0041] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0042] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0043] Embodiment 1:

[0044] Step 1: Preparation of high entropy oxide solid electrolyte dense layer

[0045] A lithium source with a purity of not less than 99wt% is selected: lithium carbonate (Li2CO3), a lanthanum source: lanthanum oxide (La2O3), a zirconium source: zirconium oxide (ZrO2), a titanium source: titanium dioxide (TiO2), and a vanadium source: vanadium oxide (V2O5) to prepare a high entropy oxide solid electrolyte dense layer.

[0046] After mixing the above raw materials, add an appropriate amount of isopropanol or ethanol as a dispersant, and use zirconium balls for wet ball milling. The ball milling process is set at a speed of 400r / min and lasts for 12 hours to obtain a uniform high entropy electrolyte drive body powder.

[0047] The obtained high entropy garnet precursor powder is placed in a furnace and calcined in an air atmosphere at a calcination temperature of 850° C., a heating rate of 3-5° C. / min, and a holding time of 6 hours.

[0048] The high entropy electrolyte powder obtained by calcination is evenly mixed with an appropriate amount of a binder (such as polyvinyl alcohol or sodium polyacrylate), and is pressed into shape using a cold pressing pressure of 30 to 50 MPa.

[0049] The formed electrolyte green body was sintered at 1000°C for 12 hours and then slowly cooled to room temperature to obtain the final LLZTVO high entropy garnet solid electrolyte ceramic.

[0050] Step 2: Prepare an amorphous aluminum oxide (Al2O3) buffer layer on one side

[0051] The surface of LLZTVO was cleaned using a plasma cleaner to remove surface impurities and ensure that the substrate surface was free of contamination.

[0052] An aluminum metal target (Al) with a purity of 99.9% or more was used as a target, which was installed at the target position of the sputtering equipment, and the distance between the target and the substrate was adjusted to 15 to 30 mm.

[0053] LLZTVO was placed on the substrate of the sputtering equipment, and the working pressure of the sputtering chamber was set to 2-5 mTorr, and oxygen was introduced. The sputtering power was set to 150 W, and the substrate temperature was maintained at 70°C. The sputtering time was controlled to 15 minutes, and the thickness of the prepared amorphous aluminum oxide Al2O3 electrolyte buffer layer was 300 nm.

[0054] Annealing at room temperature for 10 to 20 minutes can optimize the film structure, reduce stress and improve film quality.

[0055] Step 3: Preparation of sandwich structure high entropy all-solid electrolyte film

[0056] A second amorphous aluminum oxide Al2O3 electrolyte buffer layer was prepared on the other side of LLZTVO using the same process and parameters as step 2. A complete sandwich structure high entropy all-solid electrolyte film was obtained with the structure of Al2O3 (300nm) | LLZTVO (1μm) | Al2O3 (300nm).

[0057] Step 4: Low temperature sintering integrated heat treatment

[0058] Inert gas (such as nitrogen, argon) is introduced into the tube furnace, the sintering temperature is set to 200°C, the heating rate is 5°C / min, and the target temperature is maintained for 3 hours to promote ion diffusion between films and improve interface stability. After sintering, the temperature is gradually reduced to room temperature, and the cooling rate is controlled at 5°C / min.

[0059] Embodiment 2:

[0060] Step 1: Preparation of high entropy oxide solid electrolyte dense layer

[0061] A lithium source with a purity of not less than 99wt% is selected: lithium carbonate (Li2CO3), a lanthanum source: lanthanum oxide (La2O3), a zirconium source: zirconium oxide (ZrO2), a titanium source: titanium dioxide (TiO2), and a vanadium source: vanadium oxide (V2O5) to prepare a high entropy oxide solid electrolyte dense layer.

[0062] After mixing the above raw materials, add an appropriate amount of isopropanol or ethanol as a dispersant, and use zirconium balls for wet ball milling. The ball milling process is set at a speed of 400r / min and lasts for 12 hours to obtain a uniform high entropy electrolyte drive body powder.

[0063] The obtained high entropy garnet precursor powder is placed in a furnace and calcined in an air atmosphere at a calcination temperature of 850° C., a heating rate of 3-5° C. / min, and a holding time of 6 hours.

[0064] The high entropy electrolyte powder obtained by calcination is evenly mixed with an appropriate amount of a binder (such as polyvinyl alcohol or sodium polyacrylate), and is pressed into shape using a cold pressing pressure of 30 to 50 MPa.

[0065] The formed electrolyte green body was sintered at 1000°C for 12 hours and then slowly cooled to room temperature to obtain the final LLZTVO high entropy garnet solid electrolyte ceramic.

[0066] Step 2: Prepare an amorphous silicon oxide (SiO2) buffer layer on one side

[0067] The surface of LLZTVO was cleaned using a plasma cleaner to remove surface impurities and ensure that the substrate surface was free of contamination.

[0068] A silicon metal target (Si) with a purity of 99.9% or more is used as a target, which is installed in the target position of the sputtering equipment, and the distance between the target and the substrate is adjusted to 15 to 30 mm.

[0069] LLZTVO was placed on the substrate of the sputtering equipment, and the working pressure of the sputtering chamber was set to 2-6 mTorr, and oxygen was introduced. The sputtering power was set to 200 W, and the substrate temperature was maintained at 70°C. The sputtering time was controlled to 15 minutes, and the thickness of the prepared amorphous aluminum oxide SiO2 electrolyte buffer layer was 400 nm.

[0070] Annealing at room temperature for 20 to 30 minutes can optimize the film structure, reduce stress and improve film quality.

[0071] Step 3: Preparation of sandwich structure high entropy all-solid electrolyte film

[0072] A second amorphous aluminum oxide SiO2 electrolyte buffer layer was prepared on the other side of LLZTVO using the same process and parameters as in step 2. A complete sandwich structure high entropy all-solid electrolyte film was obtained, with the structure of SiO2 (400nm) | LLZTVO (1μm) | SiO2 (400nm).

[0073] Step 4: Low temperature sintering integrated heat treatment

[0074] Inert gas (such as nitrogen, argon) is introduced into the tube furnace, the sintering temperature is set to 400°C, the heating rate is 5°C / min, and the target temperature is maintained for 3 hours to promote ion diffusion between films and improve interface stability. After sintering, the temperature is gradually reduced to room temperature, and the cooling rate is controlled at 5°C / min.

[0075] Embodiment 3:

[0076] Step 1: Preparation of high entropy oxide solid electrolyte dense layer

[0077] A lithium source with a purity of not less than 99wt% is selected: lithium carbonate (Li2CO3), a lanthanum source: lanthanum oxide (La2O3), a zirconium source: zirconium oxide (ZrO2), a titanium source: titanium dioxide (TiO2), and a vanadium source: vanadium oxide (V2O5) to prepare a high entropy oxide solid electrolyte dense layer.

[0078] After mixing the above raw materials, add an appropriate amount of isopropanol or ethanol as a dispersant, and use zirconium balls for wet ball milling. The ball milling process is set at a speed of 400r / min and lasts for 12 hours to obtain a uniform high entropy electrolyte drive body powder.

[0079] The obtained high entropy garnet precursor powder is placed in a furnace and calcined in an air atmosphere at a calcination temperature of 850° C., a heating rate of 3-5° C. / min, and a holding time of 6 hours.

[0080] The high entropy electrolyte powder obtained by calcination is evenly mixed with an appropriate amount of a binder (such as polyvinyl alcohol or sodium polyacrylate), and is pressed into shape using a cold pressing pressure of 30 to 50 MPa.

[0081] The formed electrolyte green body was sintered at 1000°C for 12 hours and then slowly cooled to room temperature to obtain the final LLZTVO high entropy garnet solid electrolyte ceramic.

[0082] Step 2: Prepare an amorphous aluminum fluoride (AlF3) buffer layer on one side

[0083] The surface of LLZTVO was cleaned using a plasma cleaner to remove surface impurities and ensure that the substrate surface was free of contamination.

[0084] An aluminum metal target (Al) with a purity of 99.9% or more was used as a target, which was installed at the target position of the sputtering equipment, and the distance between the target and the substrate was adjusted to 15 to 30 mm.

[0085] LLZTVO was placed on the substrate of the sputtering equipment, and the working pressure of the sputtering chamber was set to 2-4 mTorr, and fluorine gas (F2) or fluoride gas (such as hydrogen fluoride) was introduced. The sputtering power was set to 200 W, and the substrate temperature was maintained at 120°C. The sputtering time was controlled to 30 minutes, and the thickness of the prepared amorphous AlF3 electrolyte buffer layer was 400 nm.

[0086] Annealing at room temperature for 30 min optimized the film structure, reduced stress and improved film quality.

[0087] Step 3: Preparation of sandwich structure high entropy all-solid electrolyte film

[0088] A second amorphous AlF3 electrolyte buffer layer was prepared on the other side of LLZTVO using the same process and parameters as in step 2. A complete sandwich structure high entropy all-solid electrolyte film was obtained, with the structure of AlF3 (400nm) | LLZTVO (1μm) | AlF3 (400nm).

[0089] Step 4: Low temperature sintering integrated heat treatment

[0090] Inert gas (such as nitrogen, argon) is introduced into the tube furnace, the sintering temperature is set to 400°C, the heating rate is 5°C / min, and the target temperature is maintained for 4 hours to promote ion diffusion between films and improve interface stability. After sintering, the temperature is gradually reduced to room temperature, and the cooling rate is controlled at 5°C / min.

[0091] Embodiment 4:

[0092] Step 1: Preparation of high entropy oxide solid electrolyte dense layer

[0093] A lithium source with a purity of not less than 99wt% is selected: lithium carbonate (Li2CO3), a lanthanum source: lanthanum oxide (La2O3), a zirconium source: zirconium oxide (ZrO2), a titanium source: titanium dioxide (TiO2), and a vanadium source: vanadium oxide (V2O5) to prepare a high entropy oxide solid electrolyte dense layer.

[0094] After mixing the above raw materials, add an appropriate amount of isopropanol or ethanol as a dispersant, and use zirconium balls for wet ball milling. The ball milling process is set at a speed of 400r / min and lasts for 12 hours to obtain a uniform high entropy electrolyte drive body powder.

[0095] The obtained high entropy garnet precursor powder is placed in a furnace and calcined in an air atmosphere at a calcination temperature of 850° C., a heating rate of 3-5° C. / min, and a holding time of 6 hours.

[0096] The high entropy electrolyte powder obtained by calcination is evenly mixed with an appropriate amount of a binder (such as polyvinyl alcohol or sodium polyacrylate), and is pressed into shape using a cold pressing pressure of 30 to 50 MPa.

[0097] The formed electrolyte green body was sintered at 1000°C for 12 hours and then slowly cooled to room temperature to obtain the final LLZTVO high entropy garnet solid electrolyte ceramic.

[0098] Step 2: Prepare one side LiPON electrolyte buffer layer

[0099] The surface of LLZTVO was cleaned using a plasma cleaner to remove surface impurities and ensure that the substrate surface was free of contamination.

[0100] Use Li3PO4 with a purity of more than 99.9% as the target, install it in the target position of the sputtering equipment, and adjust the distance between the target and the substrate to 15 to 30 mm.

[0101] Place LLZTVO on the substrate of the sputtering equipment and set the vacuum degree of the sputtering chamber to 1.0×10 -4 Pa, a mixed gas of argon and oxygen (volume ratio of 0.5:1) was introduced. The sputtering power was set to 50W, and the substrate temperature was maintained at 70°C. The sputtering time was controlled to 15 minutes, and the thickness of the prepared LiPON electrolyte buffer layer was 300nm.

[0102] Annealing at room temperature for 10 to 20 minutes can optimize the film structure, reduce stress and improve film quality.

[0103] Step 3: Preparation of sandwich structure high entropy all-solid electrolyte film

[0104] Using the same process and parameters as step 2, a second LiPON electrolyte buffer layer was prepared on the other side of LLZTVO. A complete sandwich structure high entropy all-solid electrolyte film was obtained, with the structure of (1μm)|LiPON(300nm)|LLZTVO(1μm)|LiPON(300nm)

[0105] Step 4: Low temperature sintering integrated heat treatment

[0106] Inert gas (such as nitrogen, argon) is introduced into the tube furnace, the sintering temperature is set to 400°C, the heating rate is 5°C / min, and the target temperature is maintained for 4 hours to promote ion diffusion between films and improve interface stability. After sintering, the temperature is gradually reduced to room temperature, and the cooling rate is controlled at 5°C / min.

[0107] Example 5: Changing the thickness of the high entropy oxide solid electrolyte dense layer to 0.4 μm.

[0108] Example 6: Changing the thickness of the high entropy oxide solid electrolyte dense layer to 2 μm.

[0109] Comparative Example 1: Compared with Example 1, in Comparative Example 1, no LiPON buffer layer is prepared, and only a high-entropy inorganic solid electrolyte is prepared. The specific preparation process is the same as that of Example 1.

[0110] Comparative Example 2: Compared with Example 1, the low-temperature sintering heat treatment process in step 4 is not performed in Comparative Example 2, and the rest is the same as Example 1.

[0111] Comparative Example 3: Compared with Example 1, the amorphous electrolyte buffer layer in Comparative Example 3 is not deposited by magnetron sputtering, but by conventional ball milling. The rest of the process is the same as that in Example 1.

[0112] Comparative Example 4: Compared with Example 1, high entropy treatment is not performed in Comparative Example 4, and the composition of the garnet-type solid electrolyte used is traditional LLZT. The rest of the process is the same as that of Example 1.

[0113] The chemical and physical properties of the electrolyte films obtained in the examples and comparative examples were measured. The following performance measurements were performed using currently available related measurement methods, which will not be described in detail here. The measurement results are shown in Table 1.

[0114] Table 1

[0115]

[0116] As shown in Table 1, in terms of electrochemical performance, the ionic conductivity of the electrolyte films obtained in Examples 1 to 6 can reach up to 2.3×10-3 S / cm, the electrochemical stability and electronic conductivity are at a high level, and the interface resistance is also low. In Comparative Example 1, only a garnet-type oxide solid electrolyte is prepared. Although the garnet-type oxide solid electrolyte is subjected to high entropy treatment in Comparative Example 1, its ionic conductivity is significantly lower than that of each embodiment, and its electrochemical stability is also significantly poor, and the interface resistance is much greater than that of each embodiment. It can be seen that the conductivity and electrochemical stability of the electrolyte film are significantly inferior to those of the sandwich structure film when only high entropy treatment is performed. In Comparative Example 2, no low-temperature sintering heat treatment is performed, and the ionic conductivity of the obtained electrolyte film is lower than that of each embodiment, the electrochemical stability is also reduced, the thermal stability and electronic conductivity are lower than those of each embodiment, and the interface resistance is also increased. In Comparative Example 3, conventional ball milling is used instead of magnetron sputtering deposition in the embodiment of the present invention, and the chemical properties are also significantly worse than those of the embodiment. Similarly, in Comparative Example 4, high entropy treatment is not performed, but traditional LLZT is used as a component of the garnet-type solid electrolyte, and the chemical properties are also significantly reduced.

[0117] The inventors also studied the tensile properties of the electrolyte films obtained in various embodiments and comparative examples. In comparative example 1, since an amorphous electrolyte buffer layer was not deposited on both sides of the garnet oxide solid electrolyte layer, its Young's modulus was much higher than that of the various embodiments, and its brittle fracture property was worse than that of the various embodiments. Although an amorphous electrolyte buffer layer was deposited in comparative examples 2, 3, and 4, the Young's modulus was also higher than that of the various embodiments. It can be seen that the all-solid electrolyte film obtained by the present invention is significantly better than the materials obtained in various comparative examples in terms of comprehensive properties such as ionic conductivity, interface contact, and mechanical properties.

[0118] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An all-solid electrolyte film, characterized in that: It includes a garnet oxide solid electrolyte layer and an amorphous electrolyte buffer layer. The garnet oxide solid electrolyte layer is a high entropy electrolyte layer. The amorphous electrolyte buffer layer is deposited on both sides of the garnet oxide solid electrolyte layer to form an electrolyte film with a sandwich structure.

2. An all-solid electrolyte film according to claim 1, characterized in that: The composition of the garnet-type oxide solid electrolyte layer is Li 6.4 LqCy 1.2 Ti 0.8 V 0.8 O 12 .

3. The all-solid electrolyte film according to claim 1, characterized in that: The amorphous electrolyte buffer layer is a buffer layer of any one of amorphous LiPON, aluminum oxide, silicon oxide, and aluminum fluoride; Preferably, the aluminum oxide is aluminum oxide, and the silicon oxide is silicon dioxide.

4. The all-solid electrolyte film according to claim 1, characterized in that: The thickness of the garnet oxide solid electrolyte layer is 0.4-2 μm, and the thickness of the amorphous electrolyte buffer layer is 300-500 nm.

5. An all-solid electrolyte film according to any one of claims 1 to 4, characterized in that: The amorphous electrolyte buffer layer is deposited by magnetron sputtering.

6. The method for preparing an all-solid electrolyte film according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) preparing a high entropy garnet solid electrolyte layer; (2) using the prepared high entropy garnet solid electrolyte layer as a substrate, magnetron sputtering deposition is performed on both sides of the substrate to form an amorphous electrolyte buffer layer, thereby obtaining a sandwich-structured electrolyte film; (3) The sandwich structure electrolyte film obtained above is subjected to low-temperature sintering heat treatment to obtain an all-solid electrolyte film.

7. The method for preparing an all-solid electrolyte film according to claim 6, characterized in that: The process in step (1) is: According to the formula of the garnet-type oxide solid electrolyte layer, raw materials are weighed; The raw materials are mixed, wet ball-milled, and then dried to obtain uniform high-entropy garnet precursor powder; The precursor powder is calcined at 850-900°C for 6 hours, with the heating rate controlled at 3-5°C / min, to obtain a calcined powder; The calcined powder is mixed with a binder and then cold pressed at 30-50 MPa to form a mold, sintered at 1000-1100° C. for 8-12 hours, and then cooled to room temperature.

8. The method for preparing an all-solid electrolyte film according to claim 6, characterized in that: In step (2), the temperature of the high entropy garnet solid electrolyte layer as the substrate is 50 to 120° C.; And / or, during the magnetron sputtering deposition process, the sputtering power is 50 to 200 W and the deposition time is 15 to 30 minutes.

9. The method for preparing an all-solid electrolyte film according to claim 6, characterized in that: After magnetron sputtering is completed, the deposited film is annealed at room temperature for 10 to 30 minutes.

10. The method for preparing an all-solid electrolyte film according to claim 6, characterized in that: During the low-temperature sintering heat treatment in step (3), the sintering temperature is 200-500° C. and the time is 1-4 hours.